Computer Self-Efficacy and Attitude Towards e-learning: A Study Among Graduate Students in Nursing in an Open University in the Philippines - Roxas-Ridulme, Queenie (International Journal on Open and Distance e-Learning, 2017)
With the advent of computer technologies and Internet, the University of the Philippines Open University (UPOU) has adopted online teaching and learning making education more accessible to students using the Internet. This study investigated the computer self-efficacy and attitudes of Master of Arts in Nursing graduate students towards e-learning. Results showed that the students’ computer self-efficacy skills were high in their beginning skills and rated fairly in their advanced skills. The students were also very confident in using their computers and had a positive attitude towards their learning through the Internet. The findings also revealed that there was no significant relationship between the students’ computer self-efficacy skills and attitude towards e-learning with a p-value of 0.902. This means that the students’ positive attitude towards e-learning does not affect their computer self-efficacy skills. It was concluded that even if the students have beginning skills in using their computers, they still feel positive in their studies.